Blood Glucose Levels on Sleep Quality in Patients with Diabetes Mellitus: A Cross-Sectional Study - Dewi Nurhanifah; Zusana A Sasarari; Awatiful Azza; Syaharuddin Syaharuddin; Muh Yunus (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Diabetes mellitus patients' blood glucose levels have a significant influence on their sleep quality. When blood glucose levels increase or decrease suddenly, people with diabetes may feel uncomfortable and experience sleep disturbances. This study aims to determine the relationship of blood glucose levels to the quality of sleep of patients with Diabetes Mellitus. Quantitative research with correlational research design cross-sectional study approach. The number of samples used amounted to 40 people with a total sampling technique. The data results from statistical tests were not normally distributed due to the value of 0.001 in blood sugar levels and 0.000 in sleep quality. Bivariate test with parametric test with Spearman's rho because this data is not normally distributed. The results between blood sugar levels and sleep quality have a value of 0.693. It can be concluded that there is no unidirectional relationship between blood sugar levels and sleep quality. It is important to understand how they influence each other in managing diabetes and overall health. The management of diabetes and sleep quality involves a holistic and individualized approach that includes lifestyle changes, dietary adjustments, and appropriate medication measures.